Dossier: Episodes of Latin American Literary History from Intellectual Networks and Archives (Palimpsesto, 2020)
Presentation Dossier: Episodes of Latin American Literary History from Intellectual Networks and Archives
Keywords: Literary History; intellectual networks; archive